2014
DOI: 10.3168/jds.2014-8098
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of roughages and concentrates relative to that of milk replacer increases strongly with age in veal calves

Abstract: We aimed to investigate the feeding values of milk replacer (MR), roughage, and concentrates for veal calves in a paired-gain setting, thus avoiding any prior assumptions in feeding values and major differences in nutrient intakes. One hundred sixty male Holstein-Friesian calves at 2 wk of age and 45 ± 0.2 kg of body weight (BW) were included in the experiment. Calves were allocated to pens (5 calves per pen) and pens were randomly assigned to 1 of 4 solid feed (SF) levels: SF1, SF2, SF3, or SF4, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…The only findings in favor of the overloading theory are 3 articles providing some indirect evidence: Veissier et al (1998) found that group-housed calves that (probably) drank their MR meal faster had more pyloric lesions than individually housed calves that (probably) drank their MR slower; and Bähler et al (2010) and Welchman and Baust (1987) found that the heaviest calves, hence possibly dominant, faster-drinking calves, developed the most pyloric (but not fundic) lesions. Two articles opposing the overloading theory are Berends et al (2014), who found that decreasing milk meal size while simultaneously increasing the concentrate part of the diet caused worse damage (experimental study), and Brscic et al (2011), who found that calves receiving relatively low amounts of MR had a higher risk for lesions (risk assessment study).…”
Section: Milk Replacermentioning
confidence: 99%
See 1 more Smart Citation
“…The only findings in favor of the overloading theory are 3 articles providing some indirect evidence: Veissier et al (1998) found that group-housed calves that (probably) drank their MR meal faster had more pyloric lesions than individually housed calves that (probably) drank their MR slower; and Bähler et al (2010) and Welchman and Baust (1987) found that the heaviest calves, hence possibly dominant, faster-drinking calves, developed the most pyloric (but not fundic) lesions. Two articles opposing the overloading theory are Berends et al (2014), who found that decreasing milk meal size while simultaneously increasing the concentrate part of the diet caused worse damage (experimental study), and Brscic et al (2011), who found that calves receiving relatively low amounts of MR had a higher risk for lesions (risk assessment study).…”
Section: Milk Replacermentioning
confidence: 99%
“…In some cases, the stress-induced lesions of monogastrics resemble the ulcers found in the calf fundus (Welchman and Baust, 1987). Therefore, many authors have noted that stress may be a predisposing or even causal factor for ulceration in calves as well (Tulleners and Hamilton, 1980;Lourens et al, 1985;Wiepkema, 1985;Welchman and Baust, 1987;Wiepkema et al, 1987;Breukink et al, 1989;Mills et al, 1990;Lallès and Toullec, 1998;Stokka and Perino, 2000;Ahmed et al, 2002;Constable et al, 2005;Marshall, 2009;Van Immerseel et al, 2010;Sasaki et al, 2012;Valgaeren et al, 2013;Webb et al, 2013;Berends et al, 2014;Çatik et al, 2015). Proposed pathways through which stress could cause abomasal damage have a common starting point, whose involvement has been demonstrated only in rats.…”
Section: The Factor Of Stressmentioning
confidence: 99%
“…The calves in the current study were selected from another experiment, which has been described by Berends et al (2014). In short, roughage was composed of 50% corn silage (Table 2) and 50% chopped (3 ± 2 cm) wheat straw (Table 2) on a DM basis.…”
Section: Diets and Feedingmentioning
confidence: 99%
“…Notably, the total-tract digestibility of NDF increased significantly with BW from 46 at 108 kg of BW to 56% at 164 kg of BW. This increase in digestion efficiency with age or BW was later also demonstrated by Berends et al (2014a).…”
Section: Nutrients From Rumen Fermentationmentioning
confidence: 53%